(untitled) (Bangladesh Journal of Plant Taxonomy, 2005)
Not available. Key words: Wedelia trilobata (L.) A.S. Hitchc.; Asteraceae; new record; Bangladesh DOI: 10.3329/bjpt.v12i1.612 Bangladesh J. Plant Taxon. 12(1): 63-65, 2005 (June)